2005
DOI: 10.1002/acp.1088
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions in appreciation of car interior design

Abstract: We report two studies in which the interplay between stimulus properties and perceiver characteristics in the appreciation car interiors was investigated. In Experiment 1 three design components, complexity, curvature and innovativeness, which are all thought to affect design appreciation were combined in a fully factorial design. All dimensions were confirmed to affect ratings, and curvature and innovativeness particularly affected the attractiveness ratings. Curved and non-innovative designs were generally p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
140
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(164 citation statements)
references
References 14 publications
15
140
2
1
Order By: Relevance
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…4). These results are consistent with evidence from previous studies establishing a preference for curved objects ranging from simple lines to furniture and car interiors (12)(13)(14)(15)(16)(17)(18)(19)(20) and the grounding of that preference in affect (16,18), and extend them to the domain of architecture. Neuroanatomically, our results demonstrated that judging the beauty of curvilinear spaces was associated exclusively with an increase in ACC activity over and above judging the beauty of rectilinear spaces (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…The results have demonstrated consistently that people typically prefer curvilinear to rectilinear objects, be they geometric forms, household objects, furniture, or car interiors (16)(17)(18), and that this effect persists even when controlling for symmetry, prototypicality, and balance (19). Furthermore, much like the earlier studies, contemporary studies have shown that curvature elicits pleasant emotions (16,18). This finding is important because it suggests that the impact of contour on judgment in the form of greater preference for curvilinear objects might be driven by an affective response to curvature.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Both studies showed participants had a higher preference for curved objects and patterns as opposed to the angular variations. Additional work relating expressly to industrial design has noted a trend in recent automotive interior design toward curved structures and away from the angularity so extensively seen in the 1980s and '90s (Leder & Carbon, 2005).…”
Section: The Character Of Formmentioning
confidence: 99%
“…Here we show, by the measurement of electrodermal activity (EDA), the need for dynamic testing, realized by the repeated evaluation technique (RET; Carbon and Leder 2005). With such a dynamic test setting we can obtain critical information about ecologically valid preferences, and, therefore, predict liking of future products (Carbon and Leder 2007).…”
Section: Introductionmentioning
confidence: 99%